Kształtowanie się tożsamości w okresie dzieciństwa i dorastania u osób z niepełnosprawnością intelektualną: rola rodziny i szkoły - Rękosiewicz, Małgorzata; Brzezińska, Anna Izabela (Wydawnictwo Naukowe UAM, 2011)
Identity is mainly formed in adolescence, but preparing for that process begins much earlier. From early childhood man gets the skills that determine the formation of identity (Erikson, 1950). The study of identity in Poland (eg. Brzezińska, Piotrowski, Garbarek-Sawicka, Karowska, Muszyńska, 2010) and around the world (eg. Luyckx, Soenens, Vansteenkiste, Goossens, Berzonsky, 2007) indicate the specific factors influencing its development, including contextual factors. The paper aims to identify the role of family and school in forming identity among young people with intellectual disability – to identify the factors that support or hinder optimal development of disability.
Identity formation in childhood and adolescence in individuals with intellectual disability: the role of family and school
Keywords: commitment; education; exploration; family; identity; intellectual disability